New cross sonic piezosonic cutting blade geometry design: pilot study - Bianca Pulino; Marcelo Pigatto D’Amado; Guilherme Louzada; Gustavo Câmara; Geraldo Prestes de Camargo Filho; Raphael Capelli Guerra (Discover Applied Sciences)
Abstract The principle of piezosurgery is “pressure electrification”. When electrical voltage is applied to certain materials such as quartz and Rochelle salts, it causes the materials to expand and contract, producing ultrasonic vibrations. This device uses ultrasonic vibration at 60–210 μm/s at 24–36 kHz to selectively remove bone with minimal damage to soft tissues such as blood vessels and nerves. In addition, it provides excellent visibility due to its cavitation effect. Piezoelectric surgery uses low-frequency ultrasonic vibration for osteotomy, which minimizes the risk of damage to soft tissue (nerves, vessels and mucosa). Micrometric vibration ensures precise cutting action and allows operative control, with consequent increased safety, in anatomical areas that are difficult to access. The aim of this study is to provide a device capable of providing a smaller contact area, less effort, lower temperature generation, faster cutting, shorter surgery time, shorter post-operative time and maxillofacial, orthopedic, neurosurgical and otorhinolaryngological procedures.